Are workers with multinational experience a determinant in startup success? - Eoin T. Flaherty (University College Dublin, UCD School of Economics, 2024)
This paper examines whether former foreign MNE workers help domestic startup firms succeed. I find evidence consistent with the idea that, as founding workers, former MNE workers positively contribute to startup outcomes. However, this appears conditional on survival. Using an event study approach on Irish administrative data, I do not find evidence that the wages of workers present from startup increase after former MNE workers join domestic firms. Likewise, there is no differential increase in size for startups joined by former MNE workers and startups that were not yet joined by former MNE workers. The same is true when examining wage outcomes at the worker level, even distinguishing between directors and non-directors, high and low wage workers. Former MNE workers are the highest earners in startups, suggesting that they have a higher ability than their peers. Challenges in adapting to a much less specialised environment and better wage bargaining may partly explain why former MNE workers do not appear to help startup firms succeed any more than other workers without this experience.
Keywords: F16; F23; J3; J6; D24; F23; J31; J60; 330; foreign direct investment; spillovers; labour mobility; linked employer-employee data; wages